Legal Evaluation of Franchise Business Contracts Using Civil Law - Laura Sharendova Gunawan (CV. Rayyan Dwi Bharata, 2023)
This study was conducted in order to learn more about the characteristics of the franchise industry and how its development relates to the rapid development of the franchise industry in Indonesia. According to the findings of the study, the franchise industry is still largely unknown among Indonesians even though it is a more profitable and capital-efficient business model than starting a new business. With certain rights and obligations carried out by each party based on the terms of the agreement set forth in the Civil Code, this franchise business can be launched immediately after an agreement is reached between the owner of the franchise right and the holder of the franchise right. franchise rights. However, apart from the basic contractual terms, the government-specific laws and regulations that serve as the legal framework for the growth of this franchise business are still very inadequate. As a result, many entrepreneurs continue to be